The international migration of women (World Bank, 2007)
The current share of women in the world's international migrant population is close to one half. Despite the great number of female migrants and their importance for the development agenda in countries of origin, there has until recently been a striking lack of gender analysis in the economic literature on international migration and development. This volume makes a valuable contribution in this context by providing eight new studies focusing on the nexus between gender, international migration, and economic development.